Production and commercialization of Smoked Liquid Sheet in the community of Jamaraquá, Tapajós National Forest (Research, Society and Development, 2020)
The Amazon has a rich biodiversity, but strong pressure is on this area, as is the case with the timber sector, with the need to seek measures to mitigate these impacts. Thus, the exploration of Non-Timber Forest Products (NTFPs) appears as an alternative, as it has a great socioeconomic and environmental potential, as is the case of the Smoked Liquid Leaf (FDL), a product derived from the processing of rubber, which has has stood out in the Amazon, mainly in the Jamaraquá community, located in the Tapajós National Forest. With that, it became necessary the quantitative and qualitative evaluation of the manufacture of FDL, as well as its uses and improvements within the Jamaraquá community. With the monitoring from the process of removing latex from the rubber tree by the community to the final product, it is evident that the processing of rubber provides the greatest added value to the product, as is the case with the use of FDL for the manufacture of bio-jewelry and shoes products with higher added value, making the sale of natural rubber less frequent and almost unviable, due to the low market value. It is clear, therefore, that Folha Defumada Net provides an important addition to the income of community members, especially when directed outside the community, and that investment in the technical training of traditional communities is shown to be advantageous, especially for the local economy.